PEMBELAJARAN SENI BUDAYA BERBASIS DEEP LEARNING DI SEKOLAH DASAR - Yessy Masida Risya; Zufriady; Mahmud Alpusari (STKIP Subang, 2026)
Cultural Arts learning in elementary schools is often focused on the final product of students’ work, resulting in limited opportunities for learners to engage in exploration, reflection, and creative development. This study describes the implementation of deep learning-based Cultural Arts instruction in an elementary school setting. A descriptive qualitative approach was employed. Data were collected through observations, interviews, and documentation at SD IT Raudatur Rahmah Pekanbaru in the even semester of the during the 2025/2026 academic year. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, while data credibility was ensured through source and technique triangulation. The findings indicate that the application of the deep learning approach promotes a more active, meaningful, and reflective learning process. Teachers functioned as facilitators who encouraged students to explore ideas, participate in discussions, and develop creativity through visual arts activities. Students demonstrated greater engagement in learning, were able to connect learning experiences with real-life contexts, and showed increased confidence in expressing their ideas through artistic works. Although several challenges were identified, including limited learning media, differences in students’ abilities, and time constraints, the deep learning approach was found to support student-centered learning, foster creativity, and enhance meaningful understanding of learning content.